2022
DOI: 10.3390/metabo12030216
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Metabolite Profiles Reflect Changes in Energy Metabolism in Heart Failure

Abstract: A variety of atherosclerosis and cardiovascular disease (ASCVD) phenotypes are tightly linked to changes in the cardiac energy metabolism that can lead to a loss of metabolic flexibility and to unfavorable clinical outcomes. We conducted an association analysis of 31 ASCVD phenotypes and 97 whole blood amino acids, acylcarnitines and derived ratios in the LIFE-Adult (n = 9646) and LIFE-Heart (n = 5860) studies, respectively. In addition to hundreds of significant associations, a total of 62 associations of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…AСs are of interest because in the field of metabolomic profiling, there is increasing evidence for the use of these metabolites as markers of CVD: insulin resistance [11], arterial hypertension [12], atrial fibrillation [13,14], CHD [15] and CHF [16][17][18]. In previous studies presented in scientific databases, we did not find a direct comparison of AC levels in patients with CHD and CHF of ischemic etiology (Table 5).…”
Section: Discussionmentioning
confidence: 71%
“…AСs are of interest because in the field of metabolomic profiling, there is increasing evidence for the use of these metabolites as markers of CVD: insulin resistance [11], arterial hypertension [12], atrial fibrillation [13,14], CHD [15] and CHF [16][17][18]. In previous studies presented in scientific databases, we did not find a direct comparison of AC levels in patients with CHD and CHF of ischemic etiology (Table 5).…”
Section: Discussionmentioning
confidence: 71%
“…Metabolic profiles are widely viewed as a molecular phenotype reflective of underlying collective information encoded at the genome level and realized at the transcriptome and proteome levels. As such, metabolic profiles have long been considered promising indicators of cancer and other complex diseases [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, various computational methods, including machine learning (ML), have been applied in efforts to identify patterns embedded within large omics datasets (e.g., genomic/proteomic/metabolomic) that may constitute an accurate diagnostic of cancer [ 5 , 6 ] and other diseases [ 7 ]. For example, perturbations of metabolic levels in the blood and/or other body fluids have long been considered promising indicators of cancer and other diseases [ 8 , 9 ] because metabolites constitute end points of many, if not most, of the molecular processes underlying biological functions. As such, metabolic profiles have been proposed as a molecular phenotype of biological systems, reflective of collective information encoded at the genome level and realized at the transcriptome and proteome levels [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have found that metabolites related to coffee intake are associated with the risk of diabetes through serum metabolomics, and these metabolites can add the predictivity of the risk of diabetes [16]. The blood metabolomics of HF patients are different from those of healthy individuals [17]. Moreover, smoking, as an important risk factor for heart failure, can cause changes in a variety of metabolites in NMR metabolomics profiling [14].…”
Section: Introductionmentioning
confidence: 99%